The effect of particle size and electrical charge on macrophage-osteoclast differentiation and bone resorption. - Sabokbar, A; Pandey, R; Athanasou, N (2003)
In aseptic loosening, there is commonly periprosthetic bone loss and a heavy macrophage infiltrate in response to biomaterial wear particles generated from the implant materials. Macrophages which have phagocytosed wear particles are known to be capable of differentiation into bone resorbing osteoclasts. In this investigation we determine the role of particle size and particle charge on this process. Mouse monocytes and macrophages were co-cultured with osteoblast-like UMR106 cells and 1,25 dihydroxyvitamin D3 in the presence or the absence of (i) various sizes of latex beads (0.1, 1, 10 and 100 microm) and (ii) uncharged, positively- or negatively-charged sephadex beads of uniform shape and composition. The extent of osteoclast differentiation by monocytes or foreign body macrophages was determined by the expression of the osteoclast-associated enzyme tartrate-resistant acid phosphatase and lacunar bone resorption. No significant difference in the extent of osteoclast formation and bone resorption was noted in response to particle size. Osteoclast formation was also not significantly different in the presence of positively/negatively charged and uncharged particles. These findings indicate that osteoclast formation is not significantly influenced by particle characteristics, such as particle size. They also add support to the hypothesis that macrophage involvement in periprosthetic osteolysis is not dependent on particle phagocytosis and that it may be induced by particle contact.